Optimalisasi Desain Visual dalam Meningkatkan Brand Awareness UMKM Anfelin Patisserie - Mutiara Putri Maharani; Sridevi Qurani; Anggi Cahyani; Zulfahmi (CV. ITTC INDONESIA, 2025)
Anfelin Patisserie, a sweet food MSME founded by Fahira Atsilah in November 2023 in GOR H. Agus Salim, Padang. Initial observations show that Anfelin Patisserie, although known for its innovative products such as the viral